Composite soy lecithin–decylpolyglucoside vesicles: A theoretical and experimental study - Mura, S. (2008)
In the present work, vesicles made with soy lecithin and a commercial mixture of alkyl polyglucosides were prepared and characterized. Vesicles with a constant amount of soy lecithin and an increasing amount of a decylpolyglucoside surfactant, (OrNS10), were formulated and their physicochemical properties were studied with the aim to design a drug delivery system suitable for different applications. To this purpose, morphology, size distribution, ζ-potential and apparent viscosity of the prepared vesicles were studied. Vesicles were also characterized by using optical and light polarized microscopy, transmission electron microscopy and photon correlation spectroscopy. A stability study was also performed by checking mean size and ζ-potential value variation of the several formulations during 4 weeks. Moreover, theoretical advances on geometric and thermodynamic aspects related to lipid vesicle formation were applied to this study. © 2007 Elsevier B.V. All rights reserved.